Farnesyltransferase inhibitors decrease matrix-vesicle-mediated mineralization in SaOS-2 cells - Tim Bürgel; Daniel Diehl; Elisabeth-Cosima van Lier; Anton Friedmann; Anna Hagemann; Hagen S. Bachmann (Molecular Biology Reports, 2026)
Background Farnesyltransferase inhibitors (FTIs) were developed for preventing the prenylation of aberrant Ras in human cancer. Furthermore, prenylation is involved in multiple biological processes and plays a putative role in signalling pathways such as the Ras-mitogen-activated-protein kinase (MAPK) pathway. Matrix-vesicle-mediated mineralization (MVM) is the first step in the development of eukaryotic mineralized tissue. In this study, we evaluated the effect of FTIs on MVM in the osteosarcoma cell line SaOS-2 and elucidated the role of farnesylation in this process. Methods SaOS-2 cells were treated with the FTIs Lonafarnib and Tipifarnib. Mineralization was assessed using Alizarin Red S staining. Enzyme assays were conducted to measure alkaline phosphatase (ALP) activity. Western blot analysis and Oxford Nanopore sequencing were performed to evaluate the expression of ALP, collagen type I (COL1A1), and Runt-related transcription factor 2 (RUNX2). Results Inhibition of farnesylation by FTIs resulted in decreased mineralization, as evidenced by reduced Alizarin Red S staining. Additionally, RUNX2 activity was diminished, leading to a reduction in MVM and decreased expression of ALP and COL1A1. Conclusion Our findings demonstrate that FTIs Lonafarnib and Tipifarnib impair MVM, highlighting the essential role of farnesylation in biomineralization.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Spraying cooling room with essential oils: effects on milk, behavior and thermal comfort - Gean Henrique Carlesso da Silva; Aleksandro S. Da Silva; Ana Luiza Bachmann Shogor; Paula Montagner; Taynara Mônica Reginatto Draszevski; Viviane Dalla Rosa; Luisa Nora; Guilherme Luiz Deolindo; Maria Luísa Appendino Nunes Zotti (Tropical Animal Health and Production, 2025)

Hydrophobic dissolved organic matter: Preferential retention in soil due to wet-dry cycles - Z. Eslamikhah; J.F. Carstens; S. Dultz; K. Zamanian; J. Bachmann; G. Guggenberger (Colloids and Surfaces C: Environmental Aspects, 2025)

Natural porcine and experimental murine influenza a virus infection – A comparative morphological approach - R. Bachmann; F. Seehusen; S. De Neck; G. Rosato; D. Mega; J. Stewart; A. Kipar (Journal of Comparative Pathology, 2025)

Integration of Design of Experiments for the Development and Evaluation of Sulfasalazine Loaded Hybrid Albumin Chitosan Based Polymeric Nanocarriers - Sushrut Marathe; Rohit Joshi; Rongbing Yang; Gauri Shadambikar; André S. Bachmann; Mahavir Bhupal Chougule (AAPS PharmSciTech, 2025)

How raw milk-based adjunct cultures influence microbial diversity in cheese - Matthias Dreier; Luca Bettera; Hélène Berthoud; Pascal Fuchsmann; Lucie K. Tintrop; Hans-Peter Bachmann; Dominik Guggisberg; Remo S. Schmidt (International Dairy Journal, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Slow-feeding dispensers for horses: Who, how and why? - M. Roig-Pons; I. Bachmann; S. Briefer Freymond (Journal of Veterinary Behavior, 2025)

Controlling Alicyclobacillus acidoterrestris spores contamination on orange surfaces using different photosensitizers and light sources - Leonardo do Prado-Silva; Guilherme Thomaz Pereira Brancini; Luciano Bachmann; Kleber Thiago de Oliveira; Gilberto Úbida Leite Braga; Anderson S. Sant’Ana (Food Control, 2025)

Removal, mechanistic and kinetic studies of Cr(VI), Cd(II), and Pb(II) cations using Fe3O4 functionalized Schiff base chelating ligands - George S. Nyamato; Ian T. Kabogo; Siphosethu Maqinana; Rene Bachmann; Markus Schmitz; Joanne Ogunah; Wolfgang Kleist; Stephen O. Ojwach (Environmental Science and Pollution Research, 2024)

Variations in water saturation states and their impact on eruption size and frequency at the Aso supervolcano, Japan - F. Keller; R.-G. Popa; J. Allaz; T. Bovay; A.-S. Bouvier; N. Geshi; A. Miyakawa; O. Bachmann (Earth and Planetary Science Letters, 2023)

Shape from spectra - Nimrod Carmon; Alexander Berk; Niklas Bohn; Phillip G. Brodrick; Jeff Dozier; Margaret Johnson; Charles E. Miller; David R. Thompson; Michael Turmon; Charles M. Bachmann; Robert O. Green; Regina Eckert; et al. (Remote Sensing of Environment, 2023)

Adsorption of Cr (VI) on lignocellulosic wastes adsorbents: an overview and further perspective - S. A. L. Bachmann; I. V. J. Dávila; T. Calvete; L. A. Féris (International Journal of Environmental Science and Technology, 2022)

Diuretics: a contemporary pharmacological classification? - Miriam C. A. Kehrenberg; Hagen S. Bachmann (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)
Diuretics are drugs that increase the flow of urine. They are commonly used to treat edema, hypertension, and heart failure. Typically, the pharmacological group consists of five classes: thiazide diuretics, loop diuretics, potassium-sparing diuretics, osmotic diuretics, and carbonic anhydrase inhibitors. This traditional classification and the nomenclature of diuretics have not changed over the last decades, which means that it was not adapted to current pharmacological research. Modern approaches in the field of pharmacological nomenclature suggest the introduction of mechanism-based drug class designations, which is not yet reflected in the group of diuretics. Moreover, included drug classes have lost their relevance as diuretic agents. Carbonic anhydrase inhibitors, for example, are mainly used in the treatment of glaucoma. Newer agents such as vasopressin-2 receptor antagonists or SGLT2 inhibitors possess diuretic properties but are not included in the pharmacological group. This review discusses the currentness of the pharmacological classification of diuretics. We elaborate changes in the field of nomenclature, the contemporary medical use of classical diuretics, and new diuretic agents.

Pharmacogenetic association of diabetes-associated genetic risk score with rapid progression of coronary artery calcification following treatment with HMG-CoA-reductase inhibitors —results of the Heinz Nixdorf Recall Study - Sonali Pechlivanis; Dominik Jung; Susanne Moebus; Nils Lehmann; Amir A. Mahabadi; Per Hoffmann; Raimund Erbel; Markus M. Nöthen; Hagen S. Bachmann (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)
HMG-CoA-Reductase inhibitors (HMGRIs) are currently the most widely used group of drugs in patients with coronary artery disease (CAD) and are given preemptively to patients with high levels of cholesterol, including those with diabetes mellitus (DM). However, intake of HMGRIs also increases the progression of coronary artery calcification (CAC) and the risk of developing DM. This study aimed to investigate whether HMGRI intake interacts with the diabetes-associated genetic risk score (GRS) to affect CAC progression using data from the population-based Heinz Nixdorf Recall (HNR) study. CAC was measured in 3157 participants using electron-beam computed tomography twice, at baseline (CAC b ) and 5 years later (CAC 5y ). CAC progression was classified as slow, expected, or rapid based on predicted values. Weighted DM GRS was constructed using 100 diabetes mellitus–associated single nucleotide polymorphisms (SNPs). We used log-linear regression to evaluate the interaction of HMGRI intake with diabetes-associated GRS and individual SNPs on CAC progression (rapid vs. expected/slow), adjusting for age, sex, and log(CAC b + 1). The prevalence of rapid CAC progression in the HNR study was 19.6%. We did not observe any association of the weighted diabetes mellitus GRS with the rapid progression of CAC (relative risk (RR) [95% confidence interval (95% CI)]: 1.01 [0.94; 1.10]). Furthermore, no indication of an interaction between GRS and HMGRI intake was observed (1.08 [0.83; 1.41]). Our analyses showed no indication that the impact of HMGRIs on CAC progression is significantly more severe in patients with a high genetic risk of developing DM than in those with a low GRS.

Obsidian pyroclasts in the Yellowstone-Snake River Plain ignimbrites are dominantly juvenile in origin - L. R. Monnereau; B. S. Ellis; D. Szymanowski; O. Bachmann; M. Guillong (Bulletin of Volcanology, 2021)
Dense, glassy pyroclasts found in products of explosive eruptions are commonly employed to investigate volcanic conduit processes through measurement of their volatile inventories. This approach rests upon the tacit assumption that the obsidian clasts are juvenile, that is, genetically related to the erupting magma. Pyroclastic deposits within the Yellowstone-Snake River Plain province almost without exception contain dense, glassy clasts, previously interpreted as hyaloclastite, while other lithologies, including crystallised rhyolite, are extremely rare. We investigate the origin of these dense, glassy clasts from a coupled geochemical and textural perspective combining literature data and case studies from Cougar Point Tuff XIII, Wolverine Creek Tuff, and Mesa Falls Tuff spanning 10 My of silicic volcanism. These results indicate that the trace elemental compositions of the dense glasses mostly overlap with the vesiculated component of each deposit, while being distinct from nearby units, thus indicating that dense glasses are juvenile. Textural complexity of the dense clasts varies across our examples. Cougar Point Tuff XIII contains a remarkable diversity of clast appearances with the same glass composition including obsidian-within-obsidian clasts. Mesa Falls Tuff contains clasts with the same glass compositions but with stark variations in phenocryst content (0 to 45%). Cumulatively, our results support a model where most dense, glassy clasts reflect conduit material that passed through multiple cycles of fracturing and sintering with concurrent mixing of glass and various crystal components. This is in contrast to previous interpretations of these clasts as entrained hyaloclastite and relaxes the requirement for water-magma interaction within the eruptive centres of the Yellowstone-Snake River Plain province.

The geometallurgical assessment of by-products—geochemical proxies for the complex mineralogical deportment of indium at Neves-Corvo, Portugal - Max Frenzel; Kai Bachmann; João R. S. Carvalho; Jorge M. R. S. Relvas; Nelson Pacheco; Jens Gutzmer (Mineralium Deposita, 2019)

Side effects of frequently used oral antidiabetics on wound healing in vitro - Ewa Klara Stuermer; M. Besser; N. Terberger; V. Koester; H. S. Bachmann; A. L. Severing (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Screening of wild potato genetic resources for combined resistance to late blight on tubers and pale potato cyst nematodes - S. Bachmann-Pfabe; T. Hammann; J. Kruse; K. J. Dehmer (Euphytica, 2019)

Aktuell - Ralf Heermann; Hagen S. Bachmann (BIOspektrum, 2018)

The dark side of zircon: textural, age, oxygen isotopic and trace element evidence of fluid saturation in the subvolcanic reservoir of the Island Park-Mount Jackson Rhyolite, Yellowstone (USA) - Juliana Troch; Ben S. Ellis; Axel K. Schmitt; Anne-Sophie Bouvier; Olivier Bachmann (Contributions to Mineralogy and Petrology, 2018)

Ex-situ evaluations of Lolium perenne L. ecotypes collected in Bulgaria, Croatia, Spain and Ireland reveal valuable breeding material - S. Bachmann-Pfabe; E. Willner; K. J. Dehmer (Genetic Resources and Crop Evolution, 2018)

The use of biotite trace element compositions for fingerprinting magma batches at Las Cañadas volcano, Tenerife - J. T. Sliwinski; B. S. Ellis; P. Dávila-Harris; J. A. Wolff; P. H. Olin; O. Bachmann (Bulletin of Volcanology, 2017)

Geochronological and isotopic records of crustal storage and assimilation in the Wolverine Creek–Conant Creek system, Heise eruptive centre, Snake River Plain - D. Szymanowski; B. S. Ellis; J. F. Wotzlaw; Y. Buret; A. von Quadt; I. Peytcheva; I. N. Bindeman; O. Bachmann (Contributions to Mineralogy and Petrology, 2016)

MeMoVolc report on classification and dynamics of volcanic explosive eruptions - C. Bonadonna; R. Cioni; A. Costa; T. Druitt; J. Phillips; L. Pioli; D. Andronico; A. Harris; S. Scollo; O. Bachmann; G. Bagheri; S. Biass; et al. (Bulletin of Volcanology, 2016)

Erupted cumulate fragments in rhyolites from Lipari (Aeolian Islands) - Francesca Forni; Ben S. Ellis; Olivier Bachmann; Federico Lucchi; Claudio A. Tranne; Samuele Agostini; Luigi Dallai (Contributions to Mineralogy and Petrology, 2015)

Groundmass crystallisation and cooling rates of lava-like ignimbrites: the Grey’s Landing ignimbrite, southern Idaho, USA - B. S. Ellis; B. Cordonnier; M. C. Rowe; D. Szymanowski; O. Bachmann; G. D. M. Andrews (Bulletin of Volcanology, 2015)

Optical Characterization of Normal, Benign, and Malignant Thyroid Tissue: A Pilot Study - M. P. Brandao; R. Iwakura; F. S. Basilio; K. Haleplian; A. S. Ito; L. C. Conti de Freitas; L. Bachmann (Journal of Fluorescence, 2015)

Hepatic 3D cultures but not 2D cultures preserve specific transporter activity for acetaminophen-induced hepatotoxicity - L. Schyschka; J. J. Martínez Sánchez; Z. Wang; B. Burkhardt; U. Müller-Vieira; K. Zeilinger; A. Bachmann; S. Nadalin; G. Damm; A. K. Nussler (Archives of Toxicology, 2013)

Aquatic Insect Assemblages of Man-Made Permanent Ponds, Buenos Aires City, Argentina - M S Fontanarrosa; M B Collantes; A O Bachmann (Neotropical Entomology, 2013)

Evolution of silicic magmas in the Kos-Nisyros volcanic center, Greece: a petrological cycle associated with caldera collapse - Olivier Bachmann; Chad D. Deering; Janina S. Ruprecht; Christian Huber; Alexandra Skopelitis; Cedric Schnyder (Contributions to Mineralogy and Petrology, 2012)

Unexpected early extinction of the European pond turtle ( Emys orbicularis ) in Sweden and climatic impact on its Holocene range - ROBERT S. SOMMER; CHARLOTTE LINDQVIST; ARNE PERSSON; HENRIK BRINGSØE; ANDERS G. J. RHODIN; NORBERT SCHNEEWEISS; PAVEL ŠIROKÝ; LUTZ BACHMANN; UWE FRITZ (Molecular Ecology, 2009)
Using ancient DNA sequences of subfossil European pond turtles ( Emys orbicularis ) from Britain, Central and North Europe and accelerator mass spectrometry radiocarbon dating for turtle remains from most Swedish sites, we provide evidence for a Holocene range expansion of the pond turtle from the southeastern Balkans into Britain, Central Europe and Scandinavia, according to the ‘grasshopper pattern’ of Hewitt. Northeastern Europe and adjacent Asia were colonized from another refuge located further east. With increasing annual mean temperatures, pond turtles reached southern Sweden approximately 9800 years ago. Until approximately 5500 years ago, rising temperatures facilitated a further range expansion up to Östergötland, Sweden (approximately 58°30′N). However, around 5500 years ago pond turtle records suddenly terminate in Sweden, some 1500 years before the Holocene thermal maximum ended in Scandinavia and distinctly earlier than previously thought. This extinction coincides with a temporary cooling oscillation during the Holocene thermal maximum and is likely related to lower summer temperatures deteriorating reproductive success. Although climatic conditions improved later again, recolonization of Sweden from southern source populations was prevented by the Holocene submergence of the previous land connection via the Danish Straits that occurred approximately 8500 years ago.

Repetitive spinal motor neuron discharges following single transcranial magnetic stimulation: relation to dexterity - W. J. Z’Graggen; A. M. Humm; S. Oppliger-Bachmann; M. Hosang; K. M. Rösler (Experimental Brain Research, 2008)

The Influence of Different Preservation and Sterilisation Steps on the Histological Properties of Amnion Allografts — Light and Scanning Electron Microscopic Studies - Frauke von Versen-Höynck; C. Syring; S. Bachmann; D.E. Möller (Cell and Tissue Banking, 2004)

Analysis of molecular data of Arabidopsis thaliana (L.) Heynh. (Brassicaceae) with Geographical Information Systems (GIS) - Matthias H. Hoffmann; Anne S. GLAß; Jürgen Tomiuk; Heike Schmuths; Reinhard M. Fritsch; Konrad Bachmann (Molecular Ecology, 2003)
A Geographical Information System (GIS) is used to analyse allelic information of 13 sequenced loci of natural populations of Arabidopsis thaliana and to identify geographical structures. GIS provides tools for visualization and analysis of geographical population structures using molecular data. The geographical distribution of the number of variable positions in the alignments, the distribution of recombinant sequence blocks, and the distribution of a newly defined measure, the differentiation index, are studied. The differentiation index is introduced to measure the sequence divergence among individual plants sampled from various geographical localities. The numbers of variable positions and the differentiation index are also used for a metadata analysis covering about 26 kb of the genome. This analysis reveals, for the first time, differences in DNA sequence structures of geographically different populations of A. thaliana . The broadly defined west Mediterranean region consists of accessions with the highest numbers of polymorphic positions followed by the west European region. The GIS technology Kriging is used to define Arabidopsis specific diversity zones in Europe. The highest genetic variability is observed along the Atlantic coast from the western Iberian Peninsula to southern Great Britain, while lowest variability is found in central Europe.

Flow Visualization in Mechanical Heart Valves: Occluder Rebound and Cavitation Potential - V. Kini; C. Bachmann; A. Fontaine; S. Deutsch; J. M. Tarbell (Annals of Biomedical Engineering, 2000)

SYFPEITHI: database for MHC ligands and peptide motifs - H. -G. Rammensee; J. Bachmann; N. P. N. Emmerich; O. A. Bachor; S. Stevanović (Immunogenetics, 1999)

Glacial survival does not matter – II: RAPD phylogeography of Nordic Saxifraga cespitosa - M. M. TOLLEFSRUD; K. BACHMANN; K. S. JAKOBSEN; C. BROCHMANN (Molecular Ecology, 1998)
It has been suggested that many arctic‐alpine plant species have limited dispersal ability and cannot have arrived in Scandinavia and the arctic archipelago of Svalbard by long‐distance dispersal after a total glaciation. It has therefore been proposed that such species must have survived the entire glaciation(s) in ice‐free refugia in southern Norway, northern Norway and Svalbard. We investigated random amplified polymorphic DNA (RAPD) variation among 28 populations from Norway and Svalbard of one of these arctic‐alpine ‘short‐distance dispersers’, the selfing polyploid Saxifraga cespitosa . In an analysis of molecular variance ( AMOVA ), more variation was found among populations within the three postulated refugia regions (45%) than among these regions (25%). Spatial autocorrelation (Mantel) analyses showed that the genetic distance monotonously increased with increasing geographical distance. In UPGMA and PCO analyses, the populations from Norway and Svalbard formed a south–north cline that continued across the Barents Sea barrier. The results suggest that there has been recent dispersal among the three postulated refugia regions and thus that postglacial dispersal into these refugia regions from other distant areas also must represent a possibility. The observed geographical pattern of the genetic variation may have been established after expansion from different source areas outside the North European ice sheet and/or from different refugia areas ‘within’ the ice sheet, but it is probably not possible to distinguish among these alternatives. The results for S. cespitosa are consistent with a dynamic late‐ and postglacial scenario with extensive plant dispersal, and support the conclusion from our previous study of the outbreeding Saxifraga oppositifolia ; the hypothesis of glacial survival in Norway and/or Svalbard is superfluous.

Integrin receptor-targeted transfer peptides for efficient delivery of antisense oligodeoxynucleotides - André S. Bachmann; Andrej Surovoy; Gunter Jung; K. Moelling (Journal of Molecular Medicine, 1998)

Glacial survival does not matter: RAPD phylogeography of Nordic Saxifraga oppositifolia - T. M. GABRIELSEN; K. BACHMANN; K. S. JAKOBSEN; C. BROCHMANN (Molecular Ecology, 1997)
The arctic‐alpine Saxifraga oppositifolia has recently been suggested to have survived the last glaciation in high‐arctic refugia, based on a finding of more genetic (RFLP) variation in Svalbard compared with more southern areas. To elucidate the migration history of this allogamous species, we analysed 18 populations from Norway, Svalbard and Novaya Zemlya using random amplified polymorphic DNAs (RAPDs). There was no more RAPD variation in the high Arctic than further south. In an analysis of molecular variance (AMOV A), most of the RAPD variation was found within populations (64%). There was less intrapopulational variation in Svalbard (65%) than in northern Norway (78%) and southern Norway (86%), suggesting that there is more inbreeding towards the north, probably because of lower pollinator activity. Twenty‐eight per cent of the RAPD variation was found among populations within these geographical regions, and only 9% was found among the regions. In PCO and UPGMA analyses, plants and populations of different geographical origins were to a large extent intermingled. There was, however, a distinct, south‐north clinal geographical structuring of the RAPD variation both in the PCO analysis and in a spatial autocorrelation (Mantel) analysis. These results suggest that there has been extensive gene flow among more or less continuously distributed populations of S. oppositifolia during the Weichselian, and that the extant Nordic populations were established after massive, centripetal immigration from these genetically variable, periglacial populations. The postglacial period may not have been sufficiently long for the subsequently isolated populations of this long‐lived, allogamous perennial to diverge. Given the high levels of migration inferred from this study, genetic differentiation of glacial survivor populations, if any existed, would most likely have been swamped in the postglacial period. Thus, our molecular data support recent conclusions based on palaeobotanical and biogeographical data that the glacial survival hypothesis is superfluous.

Glacial survival does not matter: RAPD phylogeography of Nordic Saxifraga oppositifolia - T. M. GABRIELSEN; K. BACHMANN; K. S. JAKOBSEN; C. BROCHMANN (Molecular Ecology, 1997)

Mortality of birds of prey following field application of granular carbofuran: A case study - D. R. Dietrich; P. Schmid; U. Zweifel; Ch. Schlatter; S. Jenni-Eiermann; H. Bachmann; U. Bhler; N. Zbinden (Archives of Environmental Contamination and Toxicology, 1995)

Nucleotide sequence of the coat protein gene of pelargonium leaf curl virus and comparison of the deduced coat protein amino acid sequence with those of other tombusviruses - Y. Li; S. Bachmann; E. Mai; U. Commandeur; E. Breyel; U. Timpe; R. Koenig (Archives of Virology, 1993)

Expression of the HIV-1 Nef protein in the baculovirus system: investigation of anti-Nef antibodies response in human sera and subcellular localization of Nef - N. Kienzle; M. Enders; M. Buck; H. Siakkou; S. Jahn; G. Petzold; K. E. Schneweis; M. Bachmann; W. E. G. Mller; N. Mller-Lantzsch (Archives of Virology, 1992)